Florida Crop/Pest Management Profile: Aquatic Weeds - Mark A. Mossler; Kenneth A. Langeland (EDIS)
PI-138, a 9-page fact sheet by Mark A. Mossler and Ken A. Langeland, profiles the extent of the aquatic weed infestations in Florida and current management practices and activities. Includes profiles of category I invasive plants, control methods, key contacts, and references. Published by the UF Pesticide Information Office, December 2006.